Privacy Interfaces for Collaboration - Cadiz, JJ; Gupta, Anoop (2001)
Privacy is a hot topic today in the worlds of technology, e-commerce, and public policy. However, the vast majority of the public debate about privacy has pitted the consumer against corporations and citizens against their government in terms of collecting and sharing data. While this debate is an important one, researchers should not ignore the technological advances that are providing people with the ability to share information with friends, family, and co-workers in valuable ways. Unfortunately, these technological advances have significant potential to infringe on people’s privacy, and we don’t yet know how to create interfaces that facilitate the use of these technologies while preserving people’s privacy. This paper discusses the privacy problem and results from two lab studies that explored methods to overcome this problem.